Paraffin wax microsphere embedded epoxy composites for potential thermal management in electronic devices. (September 2019) - Khagokpam, Gopal Krishna Singh; Halder, Sudipta
Miniaturization of electronic devices with more computing power has created a challenging set of aspects in thermal management. Present work is based on phase change materials microsphere and its incorporation in the epoxy network to develop a new class of potting material facilitating thermal management for miniaturized electronic devices. A facile and scalable method was implemented to synthesize paraffin wax microspheres (PMPs). It was dispersed into a room temperature curing epoxy network to fabricate the epoxy composite with high latent heat of fusion and high thermal stability. PMPs obtained have spherical morphology with an average diameter of approximately 5 µm. The PMP/epoxy composite can store 34.34 and 49.3 J g −1 of latent heat energy at 30 and 40 wt% PMP loading, respectively. Leakage test reveals that leaching declined as the size of PMP is reduced. Incorporation of PMP into the epoxy network reduces the compressive strength, but still resilient enough to protect electronic devices. This is an added advantage over the potential to mitigate the issue of hot spot in electronic devices as demonstrated by infrared thermography. The application of such composite is not limited only as electronic potting materials but also has the potential for other thermal energy storage applications.